2015
DOI: 10.1039/c4cp05575f
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic shock sensitivity in a single crystal δ-cyclotetramethylene tetranitramine: a reactive molecular dynamics study

Abstract: The anisotropic shock sensitivity in a single crystal δ-cyclotetramethylene tetranitramine (δ-HMX) was investigated using the compress-shear reactive dynamics (CS-RD) computational protocol. Significant anisotropies in the thermo-mechanical and chemical responses were found by measuring the shear stress, energy, temperature, and chemical reactions during the dynamical process for the shock directions perpendicular to the (100), (010), (001), (110), (101), (011), and (111) planes. We predict that δ-HMX is sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Molecular crystals are an important class of substances that are widely applied in pharmaceuticals, energetics, electronics, and biomaterials, among others. Plastic deformation significantly influences the preparation and application of crystals, which can induce various physical and chemical changes in a short timescale. , For example, the mechanical strength of pharmaceutical crystals can greatly be enhanced via plastic deformation during compaction into tablets . Plastic deformation and associated dislocation motion are responsible for the increased sensitivity of energetic materials to accidental initiation .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular crystals are an important class of substances that are widely applied in pharmaceuticals, energetics, electronics, and biomaterials, among others. Plastic deformation significantly influences the preparation and application of crystals, which can induce various physical and chemical changes in a short timescale. , For example, the mechanical strength of pharmaceutical crystals can greatly be enhanced via plastic deformation during compaction into tablets . Plastic deformation and associated dislocation motion are responsible for the increased sensitivity of energetic materials to accidental initiation .…”
Section: Introductionmentioning
confidence: 99%
“… where D e σ , D e π , and D e ππ are the bond parameters for σ-bonds, π-bonds, and π-π bonds, respectively; p be 1 and p be 2 are the fitting parameters. ReaxFF [ 98 , 99 , 100 ] was initially developed for simulating combustion of hydrocarbon and reactions of energetic compounds, and the functional groups such as nitro group are well-parameterized, thus various energetic compounds such as RDX, HMX, CL-20, PETN, NM, TNT, TATB, and TATP were applied [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. The ReaxFF-based MD simulations provide an efficient way to investigate the chemical reactions and other properties of various molecular crystals under particular conditions.…”
Section: Reactive Forcefields and The Applications For Emsmentioning
confidence: 99%
“…Goddard’s group has developed a ReaxFF-MD-based compress-shear reactive dynamics (CS-RD) procedure ( Figure 5 ) to investigate the anisotropic shock sensitivity of energetic crystals, in which the amount of the chemical reaction products and the kinetics were used to evaluate the sensitivity. The procedure has successfully been applied to energetic molecular crystals PETN, RDX, and HMX; as a result, it was found that the difference in internal molecular steric hindrance contributes to the origin of anisotropic sensitivity of energetic materials [ 121 , 122 , 123 , 124 , 125 , 126 ]. Special attention also has to be given to the molecular dynamics of insensitive energetic crystal TATB; therein, the shear stress, energy, temperature, and chemical reactions during compress-shear deformation were revealed under a relatively longer loading time, with the shear stress barrier found to be higher than the former energetic crystals [ 127 ].…”
Section: Reactive Forcefields and The Applications For Emsmentioning
confidence: 99%
“…Plastic deformation significantly influences the preparation and applications of crystals, which can induce various physical and chemical changes in a short timescale. 5,6 For example, the mechanical strength of pharmaceutical crystals can greatly be enhanced via plastic deformation during compaction into tablets. 7 Plastic deformation and associated dislocation motion are responsible for increased sensitivity of energetic materials to accidental initiation.…”
Section: Introductionmentioning
confidence: 99%